Hadiths About Human Intellect in the Book of Shu'ab al Iman by Imam al-Baihaqi - Adnir, Farid; Yuslem, Nawir; Nasution, Muhammad Roihan (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
This article discusses the hadith contained in the book